Phylogenomics characterization of a highly virulent Edwardsiella strain ET080813(T) encoding two distinct T3SS and three T6SS gene clusters: Propose a novel species as Edwardsiella anguillarum sp. nov - Shao, Shuai; Lai, Qiliang; Liu, Qin; Wu, Haizhen; Xiao, Jingfan; Shao, Zongze; Wang, Qiyao; Zhang, Yuanxing (Systematic and applied microbiology, 2015)
As important zoonotic organisms causing infections in humans, Edwardsiella bacteria are also notorious leading fish pathogens haunting worldwide aquaculture industries. However, the taxa are now widely recognized to be misclassified, which hurdled the understanding of the epidemiology and development of effective diagnostics and vaccines. Currently the genus Edwardsiella consists of three species Edwardsiella tarda, E. ictaluri, and E. hoshinae. Previous phylogenomic analysis revealed that E. tarda strains display two major highly divergent genomic types (genotypes), EdwGI and EdwGII, and the former represents a genotype of fish-pathogenic isolates and being recently proposed as a novel species E. piscicida, sp. nov. Here multiple phylogenetic analyses and the genome-level comparisons of EdwGI strains disclose that the phylogroup strains from diseased eel formed an obviously distinct cluster that could be equated with a new species status. The phylogenetic evidence for the new species assignment was also supported by corresponding DNA-DNA hybridization estimation values and by phenotypic characteristics. Interestingly, further comparative genomics reveals that these strains have acquired the locus of enterocyte effacement (LEE) genes and as a result these bacteria contain at least 2 sets of distinct T3SS and 3 sets of T6SS gene clusters, respectively. It is therefore proposed that the phylogroup strains from diseased eel should be classified as Edwardisella anguillarum sp. nov., and the type strain is ET080813(T) (=DSM27202(T)=CCUG 64215(T)=CCTCC AB2013118(T)=MCCC 1K00238(T)). These findings will contribute to development of species-specific control measures against Edwardsiella bacterium in aquatic animals, while also shedding light on the pathogenesis evolution in Edwardsiella bacterium.